Pengaruh Terpaan dan Kredibilitas Media Online Akun Instagram @Naikmotor Terhadap Pemenuhan Kebutuhan Followers - Gumay, Muhamad; Banowo, Emilianshah (Indonesian Journal Publisher, 2025)
This study aims to analyze the influence of media exposure and credibility on the information needs of followers of the Instagram account @naikmotor, which focuses on the automotive sector. The quantitative method was used, with data collected through questionnaires distributed to 400 respondents using a four-point Likert scale ranging from